Nasty Nazis and Extreme Americans: Cloning, Eugenics, and the Exchange of National Signifiers in Contemporary Science Fiction - Elizabeth Bridges (Studies in 20th & 21st Century Literature, 2014)
This article addresses German science fiction novels from the last ten to fifteen years, specifically those that thematize cloning and/or eugenics. The main novels under discussion include Die verbesserte Frau by Barbara Kirchner, Duplik Jonas 7 by Birgit Rabisch, and Blueprint/Blaupause by Charlotte Kerner, (which was released as a film adaptation starring Franka Potente in 2004). This discussion shows how these and similar novels do or do not contend with the legacy of Nazi eugenics and reproductive experimentation, and second, how the existent historical awareness in the novels relates to the content of debates on current issues of biotechnology, including those by Jürgen Habermas, Slavoj Zizek, and Peter Sloterdijk. The article concludes by bringing these debates to bear on cultural cross-referencing in comparative examples of American texts (Gattaca [1997], The Island [2005], to name two), which tend to imbue frightening aspects of reproductive technologies with signifiers of Nazism, while the German texts tend to implicate America as the future source of nightmarish reproductive possibilities.
Keywords: cloning; Nazism; National Socialism; genetic engineering; Gattaca; Zizek; Sloterdijk; Habermas; reproductive technologies; The Giver